Choctaw nation : a story of American Indian resurgence - Lambert, Valerie (Lincoln : University of Nebraska Press, 2007)
Choctaw Nation is a story of tribal nation building in the modern era. Valerie Lambert treats nation-building projects as nothing new to the Choctaws of southeastern Oklahoma, who have responded to a number of hard-hitting assaults on Choctaw sovereignty and nationhood by rebuilding their tribal nation. Drawing on field research, oral histories, and archival sources, Lambert explores the struggles and triumphs of a tribe building a new government and launching an ambitious program of economic development in the late twentieth century, achieving a partial restoration of the tribe's former glory as a significant political and economic presence in what is now the United States.
Introduction -- The journey has been long and hard : Choctaw culture, society, and history through 1970 -- "Because we were proud to be Choctaw" : political mobilization and the reconstitution of the tribe -- "Tomorrow is the day you are chief" : leaders, citizens, and political groups in the 1995 election -- "The first of many good things to come from the tribe" : identity, race, and economic development in Kalichito Town -- "We don't believe that claim is valid" : Choctaw sovereignty assertions and the water-rights conflict of 2001 -- Conclusion.
Includes bibliographical references (pages 279-294) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Choctaw Indians -- History; Choctaw Indians -- Social life and customs; Choctaw Indians -- Government relations; Southern States -- History; Southern States -- Social life and customs; Baseball players -- Taiwan -- History; Joueurs de base-ball -- Taiwan -- Histoire; États-Unis (Sud) -- Histoire; HISTORY -- State & Local -- General; Choctaw Indians; Choctaw Indians -- Government relations; Choctaw Indians -- Social life and customs; Manners and customs; Southern States; Choctaw (Indiens) -- Histoire; Choctaw (Indiens) -- Relations avec l'État.; Choctaw (Indiens) -- Moeurs et coutumes; Indiens d'Amérique -- États-Unis (sud); États-Unis (sud) -- Moeurs et coutumes; History